I. Seed dispersal by the critically endangered Alala (Corvus hawaiiensis). II. Integrating community values into Alala (Corvus hawaiiensis) recovery - Culliney, Susan Moana, author; Pejchar, Liba, advisor; Savidge, Julie, committee member; Bruyere, Brett, committee member (Colorado State University. Libraries, 2011)
Species loss can lead to cascading effects on communities, including the disruption of ecological processes such as seed dispersal. The endangered Alala (Corvus hawaiiensis), the largest remaining species of native Hawaiian forest bird, was once common in mesic and dry forests on the Island of Hawaii, but today exists solely in captivity. Prior to its extinction in the wild, the Alala may have helped establish and maintain native Hawaiian forest communities by dispersing seeds of a wide variety of native plants. In the absence of Alala, the structure and composition of Hawaii's forests may be changing and some large-fruited plants may be dispersal limited, persisting primarily as ecological anachronisms. I fed captive Alala a variety of native fruits, documented behaviors relating to seed dispersal, and measured the germination success of seeds that passed through the gut of Alala relative to the germination success of seeds in control groups. Alala ate and carried fourteen native fruits and provided germination benefits to several species by ingesting their seeds. My results suggest that some plants rely heavily on Alala for these services. In captivity, juvenile birds displayed seed dispersal behaviors more often than adult birds for most fruiting plants in my study. I introduced captive Alala to two large-fruited, dry forest plants, not previously recorded as Alala food resources, but which may have once been part of their natural diet. The seed dispersal behavior that Alala displayed towards these species supports the inclusion of dry and mesic forests in Alala habitat restoration plans and adds weight to the idea that plant dispersal limitation may contribute to the rarity of these plants. My study provides evidence that Alala have the capacity to play a vital role in maintaining the diversity of fruiting plants in native Hawaiian forests through seed dispersal and enhanced seed germination, thus adding greater urgency to efforts to restore Alala to their former range. Incorporating community values and perspectives into endangered species recovery programs is generally underutilized but can be an important tool for achieving conservation success. Species recovery programs adjacent to human communities can particularly benefit from integrating local perspectives on nature into program goals and practices. The Alala or Hawaiian Crow (Corvus hawaiiensis) is currently extinct in the wild but once possessed great cultural value to ancient Hawaiians and may have played a pivotal role as a seed disperser in Hawaii's forests. Past efforts to restore this charismatic bird to its historical range failed in part due to human conflict. I conducted focus group interviews in two communities bordering Alala historical range to assess participants' ability to recognize the Alala, and to understand how these community members value natural resources. I found that although very few participants recognized the Alala, many expressed curiosity and concern for the species. Participants demonstrated predominantly utilitarian views towards natural resources but these value orientations were steeped with cultural significance. Alala recovery efforts will benefit through emphasis of both the utilitarian and cultural value of this species. Reintroduction projects in Hawaii and elsewhere should dedicate a portion of their resources towards understanding the perspectives of the human communities surrounding future reintroduction sites. This approach will help avoid potential conflicts before they arise and maximize the likelihood of success by building programs based on shared values.
Seed dispersal by the critically endangered Alala (Corvus hawaiiensis)
Integrating community values into Alala (Corvus hawaiiensis) recovery